Netnographic study on the Zero Waste lifestyle : understanding motivations, challenges and strategies to maintain a zero waste lifestyle - Kläschen, Vanessa (2020)
Today’s fast pace, consumption-driven economy, and convenience of a throw-away society have led to alarming environmental issues. Large amounts of the generated garbage are going to landfills causing water pollution, increased greenhouse gas emissions and health issues while only small percentages of the garbage materials are successfully recovered and reused. To oppose this development a constantly growing consumer movement named “Zero Waste” has taken on a mindful minimalistic anti-consumerism lifestyle, to reduce their negative impact, preserve the environment and create a change in society’s mindset. While the concepts of circular economy and industrial zero waste are retrieving much attention in academic literature the academic research in zero waste as a lifestyle has been limited. Thus, this study is filling a gap and contributes to a deeper understanding of the lifestyle, members’ motivations and challenges as well as strategies of overcoming those. As the movement is global and members are gathering online to connect with likeminded people, netnography was considered as an appropriate method to conduct the study. Findings suggest that education is a key trigger for the conversion. Further, Zero Wasters boycott companies that ignore their sustainable responsibility and instead prefer to support small environmentally conscious businesses with their purchasing power. There is a shared responsibility among governments, companies, and consumers to tackle environmental issues. To maintain relevance, companies must increase transparency and rethink their product development holistically from the raw materials until the disposal and design of alternative biodegradable packaging.